2018
DOI: 10.1186/s10020-018-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-296: a promising target in the pathogenesis of atherosclerosis?

Abstract: Atherosclerosis has been recognized as an inflammatory disease involving the vascular wall. MicroRNAs are a group of small noncoding RNAs to regulate gene expression at the transcriptional level through mRNA degradation or translation repression. Recent studies suggest that miR-296 may play crucial roles in the regulation of angiogenesis, inflammatory response, cholesterol metabolism, hypertension, cellular proliferation and apoptosis. In this review, we primarily discussed the molecular targets of miR-296 inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 61 publications
(93 reference statements)
1
24
0
2
Order By: Relevance
“…It functions as a tumor suppressor in cervical, pancreatic and colorectal cancer by regulating specific targets (8)(9)(10). miR-296-3p is derived from the 3' arm of mature miR-296, and miR-296-5p is derived from the 5' arm (11). In NSCLC, miR-296-5p has been demonstrated to suppress tumor progression by targeting polo like kinase 1 (12).…”
Section: Introductionmentioning
confidence: 99%
“…It functions as a tumor suppressor in cervical, pancreatic and colorectal cancer by regulating specific targets (8)(9)(10). miR-296-3p is derived from the 3' arm of mature miR-296, and miR-296-5p is derived from the 5' arm (11). In NSCLC, miR-296-5p has been demonstrated to suppress tumor progression by targeting polo like kinase 1 (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that miR-296-5p regulates genes involved in inflammation, angiogenesis, hypertension, cholesterol metabolism, cellular proliferation, and apoptosis. Previous literature suggested it to be a promising target of atherosclerosis, an inflammatory disease in the vascular wall [27]. Given the disturbances in blood circulation and the inflammatory nature of I/R injury, it is reasonable to defer that miR-296-5p may be a key contributor to the pathogenesis of intestinal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMP23B is regulated by EPAS1 and ssc-miR-296-3p. Studies have shown that miR-296 can regulate angiogenesis [66,67].…”
Section: Discussionmentioning
confidence: 99%